The Thermal Oxidation of TiAlN High Power Pulsed Magnetron Sputtering Hard Coatings as Revealed by Combined Ion and Electron Spectroscopy. Issue 5 (19th December 2016) - Wiesing, Martin; de los Arcos, Teresa; Grundmeier, Guido
Abstract : The thermal oxidation of TiAlN hard coatings deposited by High Power Pulsed Magnetron Sputtering (HPPMS) is investigated at room temperature and 800 K at oxygen pressures ranging from 10 −6 to 10 −2 Pa by means of in situ X‐ray and Ultraviolet Photoelectron Spectroscopy as well as Low Energy Ion Scattering. The spectra reveal that oxygen binds selectively to titanium during the initial chemisorption step and simultaneously some oxygen is dissolved into subsurface layers, which stay metallic. Enhanced oxidation results into continuous formation of a multilayered oxide film including oxynitride TiAl(O, N) as a metastable reaction product buried below an oxidic top layer. This top layer is either composed of mixed TiAlO after oxidation at 800 K or of segregated TiO2 and Al2 O3 when oxidizing at 293 K. Additionally, evaluation of UV‐valence bands reveals nitrogen doping of the surface oxide films. The results are of high relevance for tailoring of the surface characteristics of TiAlN after deposition, for the design of TiAlN multilayers and for an improved understanding of the interactions of gas particles with these coatings. Abstract : The low‐temperature oxidation of TiAlN is investigated by means of electron and ion spectroscopy. The self‐limited oxygen chemisorption layer formed at room temperature and 10 −6 Pa is characterized by a 3D structure and selective binding of oxygen to titanium. Enhanced oxidation results then into a multilayered surface oxide of which the structure is controlled by the oxidation temperature.